Central corneal thickness changes and horizontal corneal diameter in premature infants - Choo, May May; Yeong, Choo Mee; Grigg, John R.; Khaliddin, Nurliza; Kadir, Azida Juana; Barnes, Elizabeth Helen; Kamalden, Tengku Ain; Watson, Stephanie L. (Lippincott, Williams & Wilkins, 2018)
To report observations of horizontal corneal diameter (HCD) and central corneal thickness (CCT) changes in premature infants with stable optic disc cupping and intraocular pressures (IOPs). The HCD and CCT at term serve as a baseline for premature infants. Sixty-three premature infants were enrolled in a prospective case series. HCD, CCT, and IOP were measured. RetCam images of the optic discs were used to evaluate the cup-disc ratio (CDR) and read by an independent masked observer. Data were collected at between preterm (32-36 weeks) and again at term (37-41 weeks) postconceptual age. Left eye measurements were used for statistical analysis. Left eye findings were combined to construct predictive models for HCD and CCT. The mean HCD was 9.1 mm (standard deviation [SD] = 0.7 mm) at preterm and 10.0 mm (SD = 0.52 mm) at term. The mean CCT preterm was 618.8 (SD = 72.9) mm and at term 563.9 (SD = 50.7) mm, respectively. The average preterm CDR was 0.31 and at maturity was 0.33. Average IOP of preterm and term was 13.1 and 14.11 mm Hg, respectively. There was significant linear correlation between HCD with the postmenstrual age (r = 0.40, P < .01) and the head circumference (r = 0.33, P < .05). Predictive models were constructed for HCD (R 2 = 0.52, 0.2 mm/wk) and CCT (R 2 = 0.23, 11.4 mm/wk) with postconceptual ages. The HCD and CCT variation did not affect IOP reading over time. CCT was not correlated with birth parameters and decreased as the infant reached term. Corneal diameter correlated with gestational age at birth and head circumference.